Significance of TNFSF11 and TNFRSF11B in Middle Ear Cholesteatoma of Children and Adults - Tang, Susu; Ye, Mingyuan; Liu, Zhao; Yang, Jing; Zheng, Zhenlin; Liu, Qianxu (ENT Updates, 2025)
Middle ear cholesteatoma is a common ear disease with different manifestations and pathological mechanisms in children and adults.Middle ear cholesteatoma is more severe in children than adults. We aimed to detect the expression of tumor necrosis factor ligand superfamily member 11 (TNFSF11) and tumor necrosis factor receptor superfamily member 11B (TNFRSF11B) and analyze the difference in ear bone destruction in middle ear cholesteatoma in children and adults.Through the comprehensive analysis of related studies, the mechanism of its action in the progression of the disease was expounded, and the theoretical basis for clinical treatment was provided. A total of 18 children and 32 adults with middle ear cholesteatomas were examined. The degree of bone destruction was observed. TNFSF11 and TNFRSF11B expressions in the cholesteatoma and normal external auditory canal skin were detected by immunohistochemistry. Bone destruction was more severe in children with middle ear cholesteatoma. TNFSF11 expression in cholesteatoma was significantly higher in children than adults, whereas expression in external auditory canal skin was not significantly different between groups. Expression of TNFRSF11B in cholesteatoma and external auditory canal skin was not significantly different between children and adults. In children and adults, TNFSF11 in cholesteatomas was not correlated with TNFRSF11B. TNFSF11 expression was positively correlated with the degree of ear bone destruction, unlike TNFRSF11B. TNFSF11 expression in children with cholesteatoma is higher than adults and is involved in the molecular biological mechanism underlying its destructive nature. These findings will help us develop better treatments.